Analysis of Fire-fighter Access as Protection against Fire Hazard in High-rise Building - Niswa Dewi A; Vinky Rahman (Talenta Publisher, 2019)
There have been many cases of fire in high-rise building occurring in the world taking a lot of casualties, some of them are the World Plasco Building in Tehran, the Grenfell Tower in London, and the Cosmopolitan of Las Vegas in Las Vegas. One of the problems that arise in many cases of fire in a high-rise building is the difficulty of access for firefighters to control fire. According to these cases, it is crucial to analyse further the access of firefighter in a high-rise building as protection against fire hazard. The study aims to find out how to assess the reliability of the fire fighting access, water supply, access aperture, and shaft of the firefighter in a high-rise building as protection against fire hazards by using the Analytical Hierarchy Process (AHP) which is sufficient to solve the problems of the reliability level of firefighters access in a high-rise building. The result is that the access of firefighter in the high-rise building on the Good level of reliability. Therefore, to improve the results of the reliability value of firefighters access in the high-rise building to be better by giving some design recommendations which according to the requirements of firefighters access. Meanwhile, the researchers can use these results of the study as reference and information for future research.